Examining the Role of Quality Assurance in Accelerating the Internationalization Process of Higher Education in Afghanistan - Faizi, Faizulhaq; Şimşek, Yücel; Rahimi, Atiqullah; Ahmadi, Ataulhaq (Journal of Social Sciences and Humanities, 2026)
Internationalization of higher education has become one of the strategic priorities for universities worldwide in recent decades; however, its effective realization largely depends on the existence of efficient quality assurance systems, Given the growing importance and discussion of quality assurance and the internationalization of higher education, to date, no specific research has been conducted on the relationship between the quality assurance process and higher education in Afghanistan. Therefore, addressing this issue is essential. This study aims to examine the role of quality assurance in supporting and strengthening the internationalization process of higher education in Afghanistan. This study is a systematic review in which data were gathered from scholarly articles, institutional reports, and policy documents published between 2006 - 2025 in databases such as Web of Science, Scopus, Wiley, Springer, Sage, Taylor & Francis, ERIC, ACE, ENQA, IEAC, Google Scholar and World Bank, and analyzed following the PRISMA guidelines. References citations have been made using Mendeley Reference Manager. The results of this research indicate that the establishment of effective quality assurance mechanisms can pave the way for increased trust and academic credibility of universities, improve the quality of teaching and research, increase participation in joint international research projects, faculty exchange, student exchange, and the internationalization of curricula. Overall, strengthening quality assurance systems can be considered one of the fundamental strategies to support the sustainable internationalization of higher education in Afghanistan.